Tradução de ficção científica: ETs e a graphic novel Protocolo Bluehand - Ecco, Josiel (2019)
This monography refers to a descriptive translation analysis of one of the chapters of the Protocolo Bluehand: Alienígena (2017), from the science fiction genre, produced by the Brazilian author Eduardo Spohr (1976). The purpose of this analysis is to verify the translation processes required during a translation; considering that from this, it is possible to disseminate national works in an international scope, so that consumers of English literature have access to Brazilian works. To achieve this goal, first, a bibliography research was carried out about the universe of Graphic Novel, having as a precursor of this genre, the American writer Will Eisner (1917-2005). Also discussed were the aspects that refer to the literary genre of science fiction and speculative fiction, besides bringing a study on the work Protocolo Bluehand: Alienígena (2017), as well as presenting considerations on the theories and procedures of the translation performed. As a result, you get a consideration of the translation choices, and the translation of the selected chapter. From all the analysis and discussion proposed in this paper, it is possible to observe that Brazilian works have market potential to be reproduced and commercialized worldwide.